Qur’anic Concepts of Human Psyche: Lahore, Pakistan. Sha‘ban 25 1409/April 3, 1989 (American Journal of Islam and Society, 1989)
During the recent past a number of Muslim psychologists in Pakistanas well as other countries have attempted to develop a greater understandingof basic Islamic sources for an alternate view of human psyche. This is anapproach which is quite new for psychologists in Muslim countries who havebeen trained in the Western intellectual tradition, and have depended on Westernsources for their methods, models and content areas of research.Since the Qur’an is the basic source of Islamic thought, it is not surprisingthat a number of Muslim psychologists have turned to the Qur’an in orderto develop an alternate perspective of understanding the human psyche.It was therefore proposed that the IIIT should help in consolidating theefforts being made in this respect by sponsoring a seminar for psychologistsinterested in this area.ObjectivesThe seminar aimed at giving the Pakistani psychologists interested inthe application of Islamic concepts in understanding human psyche an opportunityto meet and exchange ideas, and to present their views and findingsto each other and to teachers and advance students of psychology.The SeminarThe seminar was organized by the IIIT, Pakistan in collaboration withthe Department of Psychology, Government College, Lahore. This department,which is the oldest institution of post-graduate teaching and researchin psychology in Pakistan, has a strong tradition of interest in MuslimPsychology. They offer an optional course in Muslim Contributions toPsychotherapy also. The local organizer was Dr. Azhar Ali Rizvi, Chairpersonof the above department.The seminar was held on April 3, 1989 in Falleties Hotel, Lahore. Inall, 21 persons attended the delibemtions. They included eminent psychologists,social scientists and some scholars of the Holy Qur‘an. Apart from the kkhtaniparticipants, two psychologists from Dhaka University, Bangladesh read their ...